Análise do processo de logística (manipulação, armazenamento e exposição) para comercialização de hortifrutigranjeiros na feira livre Coronel Teixeira (Feira da Banana) no município de Manaus - OLIMPIO, Ericson dos Santos (Universidade Federal do Pará, 2021)
Transformations in space and in the world are known to arise from processes of production, development and commercialization in the places where they live. In this context, the fairs are considered sources of production, processing and tourism, so this research project was elaborated with the theme “Analyze the logistics process (handling, storage and exposure) for marketing of fruit and vegetables at the Banana Fair in Manaus”. Thus, the objective was to identify the preponderant legal factors that influence the marketing in the fair itself, seeking if these factors are attending the fair, to describe the process of transportation and storage of products destined to supply the fair and to propose actions of Improvements to better facilitate communication between supplier, marketer and end customer, having for this the creation of interactive application. It is possible to realize that there is a need to improve the formats and adequacy of transport used in the marketing process of products. It was also noticeable that due to inadequate transportation and poor road conditions, 30% of the produce is discarded due to the sensitivity of the products, resulting in a loss in marketers' revenue and a considerable loss in the entire production chair.